Foreign Venture Capitalists and Access to Foreign Research: The Case of US Initial Public Offerings. (12th January 2021) - Chahine, Salim; Goergen, Marc; Saade, Samer
Abstract: We investigate whether foreign venture capital (VC) firms create value above and beyond the value created by domestic VC firms in US initial public offering (IPO) firms. Contributing to an emerging literature on the role and effects of foreign VC firms, we study whether such VC firms enhance innovation by their investee firms. While high levels of innovation are a prerequisite for future value creation, as well as for maintaining the firm's competitive advantage, the extant literature nevertheless suggests that investors struggle with valuing innovation input when firms are about to go public. Ultimately, this results in greater rather than lower IPO underpricing. We argue that foreign VC firms, especially those from countries with high patent activity, increase the innovation levels of their investee firms. In turn, their presence in the VC syndicate signals the greater likelihood of the investee firm successfully turning innovation input (i.e. research and development (R&D) expenditures) into innovation output (i.e. patents), resulting in lower IPO underpricing. Studying a sample of 995 US IPOs conducted during 2000–2016, we find strong and consistent support for the above arguments.